Local-First, Global-Second: Implementing Glocal Dual Sourcing for Supply-Chain Resilience : An Exploratory Case of a Swiss Pump Manufacturer - Bureth, Lucien (My University, 2025)
Global shocks—from pandemics to geopolitics—have exposed the fragility of cost-driven global sourcing. This study asks how manufacturing firms can implement a “glocal” dual-sourcing strategy that simultaneously preserves cost competitiveness and strengthens sup-ply-chain resilience. Adopting an interpretivist, exploratory case design, we investigated a Swiss multinational that manufactures industrial pumps and vacuum systems. Six semi-structured interviews with the purchasing director, two global purchasers and three sourcing buyers provided the core data set, which was analysed thematically. Findings show that cost reduction remains the primary trigger for dual sourcing, but local suppliers become indispensable shock absorbers when global flows are disrupted. The firm follows a distinctive “local-first, global-second” sequence: collaborate with proximate suppli-ers during product development to fix design and gain internal buy-in, then add low-cost foreign suppliers for volume production. Regional purchasing hubs in China and India bridge cultural and quality gaps, while selective application—focusing on high-value or long-qualification items identified via the Kraljic matrix—keeps complexity manageable. The study contributes a directional perspective to dual-sourcing theory and offers managers a pragmatic roadmap for balancing efficiency and resilience under VUCA conditions.
Keywords: supply chains; purchases; strategies; resilience; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business